An African perspective on women’s participation in school governance - Duku, N.; Sotuku, N.; Adu, K. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Literature acknowledges the importance of women’s participation in politics in general, and particularly in school governance. However, there is evidence of women’s participation being discouraged and pushed out within both the political and societal milieu. As a result, governments have legislated women’s participation, using instruments to promote democracy and quality education for all. This article explores the approaches which African, South African women use, in negotiating democracy as citizens, to participate in school governance. Data were collected employing a qualitative approach, using in-depth interviews and participant observation. The participants were 10 black South Africans ranging in age between 40 and 65 years. The findings of a study on which this article is based, guided by Arnstein’s Ladder of Participation (1969), reflect women’s negotiation of their school governance participation in three selected South African communities. The findings are indicative of complex approaches to policy implementation in post-1994 South Africa. Since participation is mostly explored using European theories and perspectives, this study recommends the deliberate application of African theories to better understand women’s participation in African contexts. The implication of this study is that women who were young and unmarried had adopted strategies which enabled them to participate in school governance.